2018
DOI: 10.3389/fimmu.2018.02252
|View full text |Cite
|
Sign up to set email alerts
|

Phage Lysins for Fighting Bacterial Respiratory Infections: A New Generation of Antimicrobials

Abstract: Lower respiratory tract infections and tuberculosis are responsible for the death of about 4.5 million people each year and are the main causes of mortality in children under 5 years of age. Streptococcus pneumoniae is the most common bacterial pathogen associated with severe pneumonia, although other Gram-positive and Gram-negative bacteria are involved in respiratory infections as well. The ability of these pathogens to persist and produce infection under the appropriate conditions is also associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 165 publications
1
81
0
Order By: Relevance
“…This family of enzymes is widespread among viruses and can be found both in Gram-positive as well as in Gram-negative bacteria infecting phages. However, there are structural and functional differences between endolysins targeting Gram-positive and Gram-negative hosts [3,4]. Several "modes" of action are characteristic for endolysins, including the ability to hydrolyze either or both glycosidic and amide (including peptide) bonds [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This family of enzymes is widespread among viruses and can be found both in Gram-positive as well as in Gram-negative bacteria infecting phages. However, there are structural and functional differences between endolysins targeting Gram-positive and Gram-negative hosts [3,4]. Several "modes" of action are characteristic for endolysins, including the ability to hydrolyze either or both glycosidic and amide (including peptide) bonds [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most significant advantages of using endolysins as antimicrobials is their ability to quickly and effectively lyse bacteria (even antibiotic-resistant strains and bacterial biofilms) without the development of resistance [3,6]. Thus, several endolysin molecules are currently under development [4], suggesting promising results for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of literature evidences suggested that the most prevalent pathogens of URTIs include S. pneumonia, S. aureus, P. aeruginosa, E.coli, K. pneumonia and H. influenza [31], [32]. Similar bacterial pathogens have been implicated in URTIs by studies from Pakistan with minor variations in frequency distribution of bacterial pathogens [33], [34].…”
Section: Discussionmentioning
confidence: 99%
“…Lysins are peptidoglycan hydrolases that have a bactericidal effect on susceptible bacteria. They break peptidoglycan bonds, degrading the bacterial cell wall and biofilm structure [70][71][72]. This makes lysins useful for Gram-positive bacteria [73].…”
Section: Lysinsmentioning
confidence: 99%